2015
DOI: 10.1177/0308022615609623
|View full text |Cite
|
Sign up to set email alerts
|

Occupation-focused health promotion for well older people — A cost-effectiveness analysis

Abstract: Introduction: The aim of this study was to evaluate three occupational therapy interventions, focused on supporting continued engagement in occupation among older people, to determine which intervention was most cost effective, evaluated as the incremental cost/quality adjusted life year gained. Method: The study was based on an exploratory randomized controlled trial. Participants were 77-82 years, single living and without home help. One hundred and seventy seven persons were randomized to an individual inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 34 publications
0
36
0
1
Order By: Relevance
“…Four studies presented a health-economic evaluation. Three studies adopted a cost-effectiveness analysis method [13,72,102] and one a cost-utility analysis method [90]. Two studies provided an economic evaluation of single interventions; a case-management intervention [90] and an education programme for home visitors [102].…”
Section: Cost-effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies presented a health-economic evaluation. Three studies adopted a cost-effectiveness analysis method [13,72,102] and one a cost-utility analysis method [90]. Two studies provided an economic evaluation of single interventions; a case-management intervention [90] and an education programme for home visitors [102].…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Two studies provided an economic evaluation of single interventions; a case-management intervention [90] and an education programme for home visitors [102]. The other two studies compared different interventions focused on health promotion [13], and falls prevention [72]. In these four studies, a societal perspective was chosen including cost from different sectors e.g., health care and social care.…”
Section: Cost-effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of health-promoting and preventive interventions have been shown to result in positive effects for older people (Vass et al 2005;Gustafsson et al 2013;Rasinaho et al 2012;Zingmark et al 2014). If implemented, such interventions can promote health and well-being and thereby affect the expected increase in costs for health and social care (Ministry of Health and Social Affairs 2010; Zingmark et al 2016). Therefore, municipalities should consider implementing health promotion for community-dwelling older people.…”
Section: Introductionmentioning
confidence: 99%
“…Recent trials have shown that health-promoting senior meetings result in better outcomes on activities of daily living (ADL) (Gustafsson et al 2013;Zingmark et al 2014), leisure engagement (Zingmark et al 2014), self-rated health (Zingmark et al 2014), and physical function (Zidén et al 2014), compared to no intervention. In addition, groupbased interventions seem to be more effective than individual approaches (Gustafsson et al 2012;Zingmark et al 2016). These trials have adopted a single-professional (Zingmark et al 2014) or a multi-professional (Gustafsson et al 2012) design, including one (Zingmark et al 2014), four (Gustafsson et al 2013) or eight (Zingmark et al 2014) sessions, all leading to positive effects.…”
Section: Introductionmentioning
confidence: 99%